2011
DOI: 10.3904/kjim.2011.26.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance as a Risk Factor for Gallbladder Stone Formation in Korean Postmenopausal Women

Abstract: Background/AimsThe objective of this study was to determine whether insulin resistance is associated with gallbladder stone formation in Korean women based on menopausal status.MethodsThe study included 4,125 consecutive Korean subjects (30-79 years of age). Subjects who had a medical history of diabetes, hypertension, dyslipidemia, other cardiovascular disorders, or hormone replacement therapy were excluded. The women were subdivided into two groups according to their menopausal status.ResultsAnalysis of prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
1
20
0
2
Order By: Relevance
“…Yük-sek açlık glukoz düzeyleri hem karaciğerden safra asidi salgı-lanmasını hem de safra kesesinin safra sekresyonu için gerekli kontraksiyonunu inhibe etmektedir. Böylece kolesterol taşı nü-vesi oluşmakta veya oluşan nüveler üzerinde kolesterol ve safra asitleri tabakası artmaktadır [11]. Hiperglisemi safra kesesi motilitesini etkilediği gibi kolelitiazis oluşumunu ve safra kesesi mukus sekresyonunu da etkilemektedir [19][20].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Yük-sek açlık glukoz düzeyleri hem karaciğerden safra asidi salgı-lanmasını hem de safra kesesinin safra sekresyonu için gerekli kontraksiyonunu inhibe etmektedir. Böylece kolesterol taşı nü-vesi oluşmakta veya oluşan nüveler üzerinde kolesterol ve safra asitleri tabakası artmaktadır [11]. Hiperglisemi safra kesesi motilitesini etkilediği gibi kolelitiazis oluşumunu ve safra kesesi mukus sekresyonunu da etkilemektedir [19][20].…”
Section: Discussionunclassified
“…Ülkemizde MS görülme sıklığı, erkeklerde %28, kadınlarda ise %40 gibi oldukça yüksek değerlerdedir [3]. Çalışmalar MS'yi kolelitiazis için bir risk faktörü olarak öngörmektedir [9][10][11]. Umbilikal herniler, paraumbilikal herniler ve epigastrik herniler tüm karın duvarı hernilerinin %10'luk kısmını oluşturur [12].…”
Section: Introductionunclassified
“…5 Risk factors associated with GSD include female gender, age, obesity, metabolic syndrome, diabetes, hyperlipidemia, high caloric intake, and family history. [6][7][8] Identifying risk factors that can be manipulated should provide an opportunity to prevent cholelithiasis. 9 Accumulating evidence suggest that the pathogenesis of GSD is multifactorial, with both environmental and genetic factors being involved.…”
Section: Introductionmentioning
confidence: 99%
“…Gonzalez Villalpando et al [32] studied a Mexican population using gallbladder ultrasound and found that the waist to hip ratio was not related to gallbladder disease. In contrast with the aforementioned study, Kim et al [33] found a statistically significant association between the occurrence of gallbladder stones and abdominal obesity. In a population-based ultrasonographic study for gallstone disease, the waist to hip ratio was found to be related to gallbladder disease [34].…”
Section: Discussionmentioning
confidence: 87%